UPAYA MEMAKSIMALKAN HASIL BELAJAR BAHASA DAN SASTRA INDONESIA MELALUI PENERAPAN MOTIVASI, DENGAN METODE BERMAIN PERAN DAN SOSIO DRAMA SISWA KELAS XII IPS 1 DI SMA NEGERI 2 BANGKO: The Efforts to Maximize Indonesian Language and Literature Learning Outcomes through Motivation Application, with Role Play and Sosio Drama Methods of XII IPS 1 Students in SMA Negeri 2 Bangko - Rina Angriani (UIR Press, 2018)
The purpose of this study is to improve learning outcomes in Indonesian subjects on the component of the ability of literary aspects of speaking, basic competence to express the dialogue of the characters in the play, knowing the effectiveness of the application of motivation, role playing methods, and socio drama, in improving learning outcomes subjects Bahasa Indonesia , the component of the ability of bersasra, the aspect of basic competence to express the dialogue of the character's role in the drama performance, to know the influence of the application of motivation, the role playing method and the socio-drama, express the dialogue of the characters in the staging of the drama of the class XII IPS1 SMA Negeri 2 Bangko to improve the learning result of the eye Bahasa Indonesia component of literary ability, basic competence speaking aspect expressed the dialogue of the characters in the drama performance. This study uses a classroom action research design (PTK). The subjects of the study were students of SMA Negeri 2 Bangko Kabupaten Rokan Hilir The research procedure used Kemmis and Taggart model, consisting of planning, action and observation, and reflection. Technique of data taker through learning result data, learning data. The data that have been obtained are grouped, analyzed by using analysis of minimum learning mastery criteria. The research results: 1) The application of motivational approach, with role playing method and socio drama can maximize or improve learning outcomes, Indonesian subjects, component of literary ability of speaking aspect expressing dialogue of the characters in drama 2) Implementation of motivational approach, by role playing method and socio can cause a sense of appreciation of the art of staging drama in the learning of Indonesian subjects, the component of the ability of literary aspects of speaking basic competence to express the dialogue of the characters in staging drama. 3) The application of motivational approach, by role playing method and socio drama can improve cooperation and mutual respect among students in learning Indonesian subjects, component of literary ability of speaking aspect of basic competence expressing dialogue of the characters in staging drama.